The Influence of Task-Irrelevant Music on Language Processing: Syntactic and Semantic Structures - Hoch, Lisianne; Poulin-Charronnat, Benedicte; Tillmann, Barbara (Frontiers in Psychology, 2011)
Recent research has suggested that music and language processing share neural resources, leading to new hypotheses about interference in the simultaneous processing of these two structures. The present study investigated the effect of a musical chord’s tonal function on syntactic processing (Experiment 1) and semantic processing (Experiment 2) using a cross-modal paradigm and controlling for acoustic differences. Participants read sentences and performed a lexical decision task on the last word, which was, syntactically or semantically, expected or unexpected. The simultaneously presented (task-irrelevant) musical sequences ended on either an expected tonic or a less-expected subdominant chord. Experiment 1 revealed interactive effects between music-syntactic and linguistic-syntactic processing. Experiment 2 showed only main effects of both music-syntactic and linguistic-semantic expectations. An additional analysis over the two experiments revealed that linguistic violations interacted with musical violations, though not differently as a function of the type of linguistic violations. The present findings were discussed in light of currently available data on the processing of music as well as of syntax and semantics in language, leading to the hypothesis that resources might be shared for structural integration processes and sequencing.